Unconscionability in European Private Financial Transactions : Protecting the Vulnerable. - Kenny, Mel (Cambridge University Press, 2010)
This collection presents a detailed analysis of European concepts of unconscionability in financial transactions, against a backdrop of harmonisation initiatives.